A Randomized Controlled Trial of a Behavioral Economic Intervention for Alcohol and Marijuana Use - Yurasek, Ali M. (Exp Clin Psychopharmacol, 2015)
OBJECTIVE: A recent study demonstrated that a single 50-minute supplemental session that targeted the behavioral economic mechanisms of substance-free reinforcement and delayed reward discounting (Substance Free Activity Session: SFAS) enhanced the efficacy of a standard alcohol brief motivational intervention (BMI) for college drinkers. The purpose of the current study was to conduct a randomized controlled trial intended to replicate and extend the aforementioned study by focusing on both drug and alcohol misuse and reducing session length in order to enhance dissemination potential. METHOD: Participants were 97 college students (58.8% women; 59.8% white/Caucasian & 30.9% African American; M age = 20.01, SD = 2.23) who reported at least one heavy drinking episode in the past month (M = 4.01 episodes). Most participants (62%) reported recent marijuana use (M = 12.22 days of past-month use). After completing a baseline assessment and an individual 30-minute alcohol-focused BMI, participants were randomized to either the 30-minute SFAS session or an education control session. RESULTS: A series of mixed model intent-to-treat analyses revealed that both groups reported drinking reductions and that participants in the BMI+SFAS group reported fewer days using marijuana at the 6-month follow-up. CONCLUSIONS: These results do not support the incremental efficacy of the briefer SFAS for reducing drinking but suggest that it may improve marijuana outcomes. Future research is needed to identify the ideal length and timing of the SFAS supplement to BMIs.